2016
DOI: 10.4018/978-1-5225-0094-0.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring Environmental Sustainability through Sustainable Entrepreneurship

Abstract: Sustainability has become an important issue worldwide because of great concerns about the unintended social, environmental, and economic effects of increasing population and economic growth, as well as consumption of natural resources. One recent concept arising from sustainability issue is sustainable entrepreneurship which integrates both the social and environmental aspects, and linking them with entrepreneurial activities. This chapter therefore suggests that efforts of developing countries at promoting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The development of social entrepreneurship is mainly based upon the development of sustainable business models. According to Abereijo (2016), social entrepreneurs aim to design and develop a business in a way which would not only bring profit to the organization but also be beneficial for society. This might imply that the development of social entrepreneurship is not only based upon profitability but also sustainable business practices and models.…”
Section: Development Of Sustainable Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of social entrepreneurship is mainly based upon the development of sustainable business models. According to Abereijo (2016), social entrepreneurs aim to design and develop a business in a way which would not only bring profit to the organization but also be beneficial for society. This might imply that the development of social entrepreneurship is not only based upon profitability but also sustainable business practices and models.…”
Section: Development Of Sustainable Modelsmentioning
confidence: 99%
“…On the other hand, sustainable business models are also important for competitive advantage for businesses. In order to fully benefit society, a social enterprise must survive and remain profitable, which is only possible when it is operating on a sustainable business model (Abereijo 2016). Within this context, Scaffa and Reitz (2013) recommended that social entrepreneurs must develop effective business strategies to ensure that social business remains competitive and survive within a commercial context.…”
Section: Sustainable Business Modelsmentioning
confidence: 99%
“…To extend entrepreneurship research through an examination of sustainability, Juma et al (2017) conducted a study in the context of a comparison of two case studies, which resulted in the proposal of fluid and integrative multi-systems model of collaboration with various stakeholders (e.g., private and public sector, and NGOs etc.). Thompson and Scott (2010) and Abereijo (2016) also analyzed the perspective of environmental entrepreneurship and sustainable development of the global entrepreneurship using different tools of analysis, and found that global entrepreneurship is developing in an unstable way. Practical solutions are offered to resolve this issue in the study of Morozova et al (2019).…”
Section: Entrepreneurship and Its Dimensionsmentioning
confidence: 99%